The Efforts of Parents in Choosing Suitable Toys for Children Aged 3-4 Years - Ruwindah, Abroro; Handayani, Sri Sularti Dewanti (Jurusan PGPAUD FIP UNNES, 2019)
Playing is a fun activity for children and is an easy way for a child’s brain to form new memories. Playing is related to toys. Children’s toys selection is dominated by the parents’ will or vice versa that is based on the wishes of children without any attempt by parents in directing the appropriate tools for the child. This study aims to find out the efforts made by parents. The next objective is to find out the parents’ understanding of the purpose of toys that are suitable for children aged 3-4 years. Knowing the considerations made by parents as an effort to choose toys that are suitable for children aged 3-4 years in Kebumen Village, is the third goal of this study. The research method is qualitative research with the research subject is parents of 3-4 years old children, their children, and educators in Kebumen Village. Data collection techniques in this study are observation, interviews, and documentation. Data analysis methods are through the process of data collection, data reduction, data presentation, and verification of data and conclusion. Based on the research, the results show that the parents’ understanding about the purpose of the toys is as stimulation of child development. Parents’ efforts consist of children’s desires/interests and discussions with children. Those efforts are carried out mostly by parents. Considerations made by parents as part of the effort to choose children’s toys are more inclined to the price of toys than the function and purpose of education that is suitable for children aged 3-4 years. In addition, the colors and materials and labels of children’s toys by most parents are not much considered.